Community-Based Education for Family Health: Leveraging Local Medicinal Plants through Empowerment - Rahman, Asep; Jayanti, Meilani; Asaloei, Sandra Inggrid; Adam, Hilman (Journal of Literacy and Education, 2025)
The utilization of local medicinal plants remains a common practice within households in coastal areas, including Minaesa Village in North Minahasa Regency. However, such practices are generally based on intergenerational experience rather than an adequate understanding of appropriate indications, limitations, and potential risks. This community service initiative aimed to empower the community through a community-based educational approach to enhance family health literacy in the rational and safe use of local medicinal plants. The implementation methods included initial observation and needs assessment, development of evidence-based educational materials tailored to the local context, and delivery of interactive counseling sessions combined with guided discussions. Evaluation was conducted qualitatively through participants’ active engagement and reflective responses. The findings indicated improved participants’ understanding of fundamental principles for the proper use of medicinal plants, enhanced ability to identify minor conditions that may be managed at the household level, and increased awareness of warning signs requiring medical referral. This approach effectively integrated traditional knowledge with modern health literacy principles, thereby strengthening family capacity to make safer and more responsible health decisions.